A internacionalização do P&D em empresas multinacionais e a formação de empresas de base tecnológica no Brasil - Barretto, Antonio Luiz Corrêa de Mattos (2007)
This dissertation aims to evaluate technology spin-offs Brazilian economy in the context of internationalization of multinational companies. Since 1980, the multinationals modify its international production strategies stressing efforts in R&D and other high value-added activities and affiliated companies gain a more important role at the international strategy of the group. As an indirect result of the technological role of the affiliated in national economy technology spin-offs are an important subject that need to be more attention. This work analyses the chacteristics of spin-offs from different origins focusing on affiliated as the parent organization.